Applicability of Existing Crack Controlling Criteria for Structures with Large Concrete Cover Thickness - Naotunna Chavin Nilanga; Samarakoon S.M Samindi M.K; Fosså Kjell Tore (Nordic Concrete Research, 2021)
Widely used crack width calculation models and allowable crack width limits have changed from time to time and differ from region to region. It can be identified that some crack width calculation models consist with limitations for parameters like cover thickness. The current Norwegian requirement for cover thickness is larger than these limitations. The applicability of existing crack width calculation models and the allowable crack width limits must be verified for structures with large cover thickness. The background of crack width calculation models in Eurocode, Model Code 2010, Japanese code, American code and British code have been examined. By comparing the experimental crack widths with the predictions of the aforementioned models, the existing codes can be identified as requiring modification. Considering the durability aspect, it can be identified a long-term study proving that the allowable crack width can be increased with the increase in cover thickness. When considering the aesthetic aspect, the authors suggest categorizing the structures based on their prestige level and deciding the allowable crack widths accordingly. The paper proposes potential solutions for future research on how to improve both crack width calculation methods and allowable crack width limits to be used effectively in structures with large cover thickness.